(untitled) (Al-Aasar, 2025)
The function of language extends beyond merely describing the world; it also serves to transform it through speech acts, necessitating careful selection of words. Politeness strategies play a crucial role in expressing solidarity and respect, thereby fostering and sustaining positive social relationships. In academic settings, positive relations between teachers and students are linked to improved academic performance. This study investigates linguistic politeness in computer-mediated communication (CMC) in the Pakistani academic context. More specifically, this study aims to identify the politeness strategies by Pakistani students in their email requests to faculty. Employing a sequential mixed-methods research design, a corpus of 32358 tokens was compiled from the emails received by four instructors from two public-sector universities between 2021 and 2023. The selected samples from the corpus were analyzed qualitatively using Brown and Levinson’s (1978, 1987) politeness model. The qualitative findings informed the development of a hypothesis, which was subsequently tested through a computer-assisted corpus-based analysis to triangulate the results. The study addresses a gap in the literature by examining politeness in the Pakistani academic context, contributes to the expanding field of corpus-based politeness research, and offers implications for educational policymaking in Pakistan.